The Effect of Using Quizlet on Students' Vocabulary Mastery - Ramadani, Iftia Asri; Oktarini, Widya; Devanti, Yeni Mardiyana (LPPM Universitas Pahlawan Tuanku Tambusai, Riau, Indonesia, 2024)
In the 21st century, using electronic flashcard media is an option educators in Indonesia consider to provide variety in learning using existing technology. The problem of this research is